Linux bible - Negus, Christopher (New Delhi: Wiley India, 2016)
"Linux Bible, 9th Edition is the ultimate hands-on Linux user guide, whether you're a true beginner or a more advanced user navigating recent changes. This updated ninth edition covers the latest versions of Red Hat Enterprise Linux 7 (RHEL 7), Fedora 21, and Ubuntu 10.04 LTS, and includes new information on cloud computing and development with guidance on Openstack and Cloudforms. With a focus on RHEL 7, this practical guide gets you up to speed quickly on the new enhancements for enterprise-quality file systems, the new boot process and services management, firewalld, and the GNOME 3 desktop. Written by a Red Hat expert, this book provides the clear explanations and step-by-step instructions that demystify Linux and bring the new features seamlessly into your workflow"--Provided by publisher.
pt.I. Getting started. Starting with Linux ; Creating the perfect Linux desktop -- pt. II. Becoming a Linux power user. Using the shell ; Moving around the filesystem ; Working with text files ; Managing running processes ; Writing simple shell scripts -- pt. III. Becoming a Linux system administrator. Learning system administration ; Installing Linux ; Getting and managing software ; Managing user accounts ; Managing disks and filesystems -- pt. IV. Becoming a Linux server administrator. Understanding server administration ; Administering networking ; Starting and stopping services ; Configuring a print server ; Configuring a web server ; Configuring an FTP server ; Configuring a windows file sharing (Samba) server ; Configuring an NFS file server ; Troubleshooting Linux -- pt. V. Learning Linux security techniques. Understanding basic Linux security ; Understanding advanced Linux security ; Enhancing Linux security with SELinux ; Securing Linux on a network -- pt. VI. Extending Linux into the cloud. Using Linux for cloud computing ; Deploying Linux to the cloud -- pt. VII. Appendixes. Appendix A. Media ; Appendix B. Exercise answers.
Includes index.
"The comprehensive, tutorial resource : build Linux desktop, workstation, and server skills, advance to enterprise and cloud computing, become a Linux system admin or power user"--Cover.
Keywords: Linux; Operating systems (Computers); Operating systems; Linux